Use of combined oral contraceptives and risk of venous thromboembolism in young women: a nested case–control analysis using German claims data. (8th August 2022) - Schink, Tania; Princk, Christina; Braitmaier, Malte; Haug, Ulrike
Abstract: Objective: To compare the risk of venous thromboembolism (VTE) among young women for nine combined oral contraceptives (COCs), including progestogens with an as yet unclear risk of VTE such as chlormadinone and nomegestrol, using COCs containing levonorgestrel with low ethinylestradiol (<50 μg) as a reference. Design: Case–control study nested in a cohort of new users of COCs. Setting: German claims data. Population: A total of 1166 cases of VTE matched to 11 660 controls nested in a cohort of 677 331 girls and young women aged 10–19 years with one or more COCs dispensed between 2005 and 2017 after a 1‐year period without any COCs. Methods: Confounder‐adjusted odds ratios (aORs) of VTE associated with current use of the respective COCs were calculated using conditional logistic regression. Main outcome measures: Venous thromboembolism (VTE), defined as a diagnosis of pulmonary embolism or deep vein thrombosis. Results: Compared with levonorgestrel with low ethinylestradiol (<50 μg), the risk of VTE was increased two‐fold for COCs containing dienogest (aOR 2.23, 95% CI 1.77–2.80), cyproterone (aOR 2.15, 95% CI 1.43–3.25), chlormadinone (aOR 2.06, 95% CI 1.58–2.68), desogestrel (aOR 1.93, 95% CI 1.44–2.61) and drospirenone (aOR 1.89, 95% CI 1.41–2.55), and increased five‐fold for gestodene (aOR 5.05, 95% CI 1.23–20.74). For norgestimate and nomegestrol, the point estimates suggest a two‐fold increased risk (aOR 1.90, 95% CI 0.62–5.81) and 40% increased risk (aOR 1.41, 95% CI 0.52–3.81), respectively. Conclusions: Our study confirms that levonorgestrel with low ethinylestradiol (<50 μg) is the COC associated with the lowest risk of VTE and suggests that for chlormadinone the risk of VTE is two times higher, and thus in the same range as for desogestrel and drospirenone.